Kontrola czy nadzór sądu nad postępowaniem przygotowawczym - Łuszczyk, Ewelina (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The paper examines the role of the court in preliminary proceedings in the light of the Code of Criminal Procedure. The author carries out a historical-legal analysis of the impact the court has had on preliminary proceedings and discusses the functions currently assigned to it by the legislator at this particular stage of the criminal procedure. She concludes that the applicable Code of Criminal Procedure indicates the adoption of a “control-based” model of the court’s impact on preliminary proceedings.
Keywords: postępowanie przygotowawcze; sąd; kontrola; nadzór